Nasionalisme Humanistis Mahatma Gandhi - Poerbasari, Agnes Sri (UI Scholars Hub, 2007)
This article proposes to investigate how Gandhi developed the idea of humanistic nationalism and what the component of this idea is. Using the historical and political approaches, the investigation shows that Gandhian's nationalism reveals the relationship between religious aspiration, political ethic and the ideal economic and political institutions. Chronologically, this study describes Gandhi's leaderships in South Africa (1893-1914) and India (1915-1948), the basic orientation of Gandhi's thought and lastly explains the concept of humanistic nationalism. Briefly, the components of humanistic nationalism are the ideas of Hind Swaraj, Nation, Sarvodaya, Khadi Economic, Ramrajya and Panchayat Raj. Behind all those concepts is Ahimsa, the principle of no harm which emphasizes and teaches about love and non-violence. Both attributes are used as weapons by Gandhi's Satyagraha movement. Ahimsa is also the core of Gandhian political ethic and lies on his ideal economic and political institutions. By this moral effect of Ahimsa, we could easily identify Gandhi's nationalism with the unique character called humanistic.